The role of risk management of the logistic processes in economic development of the region - Freydman, Oxana (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2011)
The development of market structures occurs in conditions of uncertainty and risk, which is reflected in the activities of all stakeholders of transport and logistics system in the region. If we understand how the risk of loss or reduced income occurs, we can calculate the likelihood of it. Most important in this regard is risk prediction, since its probability can be determined, and due to the forecasts the management of territorial risks can be developed.